ANALISIS TEKNIK PENERJEMAHAN ADAPTASI DAN VARIASI PADA SUBTITLE FILM BATMAN VERSI BAHASA JAWA MATARAMAN - Anita Rahma; Diah Kristina; Sri Marmanto (Universitas Sebelas Maret, 2018)
The aim of this study is to identify and describe the cultural elements translated using adaptation technique and linguistic elements translated using variation technique in Batman movie subtitled into Mataraman Javanese. Then explain the translator’s reason of using the adaptation and variation technique, and describe the effect of both techniques towards the translation quality. This is a prescriptive qualitative study and categorized as an embedded research. The sources of data are 1) script of Batman movie and its translation in Mataraman Javanese, 2) the raters as informant who evaluate the translation in terms of accuracy and acceptability, and 3) the target audiences to rate the comprehension.Based on the research result, the researcher collected 110 data which consist of 48 adaptation data and 62 variation data. The adaptation data in this study are ecology, material culture, social culture, procedure/ activity/ artistic term, economic system and language. Meanwhile, the variation data contain the personal pronouns for first person, second person, and third person translated into speech level of ngoko (showing low politeness), madya (showing middle politeness) and krama (showing high politeness). The use of adaptation and variation techniques by the translator is in line with the purpose of Mataraman Javanese program held by local TV station to accommodate the local wisdom. For that reason, the translation ideology of this subtitle is domestication by employing those translation techniques which are closes to the target language culture. Generally, the use of adaptation and variation techniques in this study is quite accurate, acceptable in the target culture and comprehensible to the target audience.